Evaluation of Patients with Liver Injuries Treated by Perihepatic Gauze Packing - Hindosh, *Laith Naef (AL-Kindy College Medical Journal, 2008)
Background: The liver is one of the most common organs injured after blunt abdominal trauma. The control of severe hemorrhage remains a problem. Methods: One-hundred thirty-eight patients diagnosed as liver injury between 09/2003 and 08/2006 had been evaluated prospectively in Al- Kindy Teaching Hospital. A distinction was made between hemodynamically stable and unstable patients. Different modalities of surgical procedures were done concentrating on perihepatic gauze packing. Results: (60 out of 138) patients included in the study were clinically evaluated as hemodynamically stable. The average abbreviated injury severity score (ISS) was 25. Twenty patients underwent abdominal surgery. In 12 of them additional liver treatment was performed. The mortality was three, all were non-liver related. Seventy eight patients were considered to be hemodynamically unstable, and had an average ISS of 38. All of them needed abdominal surgery. Gauze packing was used as initial therapy for bleeding control from injured liver in 34 patients of both hemodynamically stable and unstable groups with a mortality of 11 patients (32.7%). Conclusion: perihepatic gauze packing is considered as a life saving and a quick method for controlling ongoing hemorrhage in the treatment of liver injuries before undertaking definitive repair under controlled conditions